MULTI-TOOL EVALUATION OF WEB ACCESSIBILITY FOR LEARNING AND DEVELOPMENT COMPANY WEBSITES. - KURANGI, CHINNA RAO (Turkish Journal of Physiotherapy Rehabilitation, 2021)
In recent days, website plays a vital role in every day's life for communication, obtaining information, etc. Web accessibility gives a way to access web resources for different people with no dependency on age, language, tradition, physical condition and so on. Worldwide accessibility of website remains a bigger challenge for web developers and research people. Several studies have been done to assess the web accessibility of diverse websites. Recently, learning and development company websites gains popularity since the learning process begins with these types of websites. Few of these companies include Harvard business, safety media, degreed, Lynda, etc. Since e-learning domain is highly helpful for students across various levels, it is essential to access those websites for accessibility. The accessibility of websites has been evaluated through W3C standard guidelines with the help of multi-tool. This paper presents a multi-tool accessibility analysis of Best Learning company websites. A comparative analysis of five accessibility tools is also presented with 13 dissimilar parameters. In this study, 100 learning and development company websites are assessed using five evaluation tools namely EvalAccess2.0, Run FAE, TAW, Tenon and Hera. These tools give us the results of selected websites accessibility position on Web Content Accessibility Guidelines (WCAG 1.0 and WCAG 2.0). The performance evaluation indicates that the websites should be improved so that it can be accessible worldwide.